Visual and Emotional Connections in Wooden Product Design: A Comprehensive Review of Neuro-architecture Principles - Dharsono, Wardhana Wahyu (Journal of Artificial Intelligence in Architecture, 2025)
This systematic review investigates the integration of neuro-architecture principles in wooden product design, focusing on visual-emotional connections between users and wood materials. Through analysis of 134 studies incorporating neuroimaging techniques (fMRI, EEG) and psychological assessments, this review synthesises the current understanding of how wood's visual and tactile properties influence neural responses and emotional engagement. Key findings reveal that specific wood characteristics trigger distinct neural activation patterns: natural grain patterns activate the anterior insula and amygdala regions associated with emotional comfort, while different wood colours elicit varying responses in the prefrontal and posterior cingulate cortex, affecting alertness and calmness. Light-coloured woods promote openness and energy, while darker tones enhance focus and intimacy. The research establishes evidence-based design guidelines for optimising visual complexity, colour temperature balance, pattern rhythm, and texture gradients. These findings provide designers with neurologically informed strategies for creating wooden products that enhance psychological well-being. The review identifies future research directions, including the need for longitudinal studies and cross-cultural investigations, while acknowledging current methodological limitations. This comprehensive analysis bridges neuroscientific evidence with practical design applications, advancing the field of neuroarchitecture-informed wooden product design.